2014
DOI: 10.1093/neuonc/nou283
|View full text |Cite
|
Sign up to set email alerts
|

The worldwide incidence and prevalence of primary brain tumors: a systematic review and meta-analysis

Abstract: There is a need for more accurate and comparable incidence and prevalence estimates of primary brain tumors across the world. A standardized approach to the study of the epidemiology of these tumors is needed to better understand the burden of brain tumors and the possible geographical variations in their incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
171
3
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(192 citation statements)
references
References 61 publications
3
171
3
15
Order By: Relevance
“…Although some previous reports suggested sex diff erences in the occurrence of primary brain tumors, a recent study by de Robles et al indicated no statistically signifi cant gender diff erence in the overall estimate of brain tumors 27,28 . Th e most common tumor found in our study was an unclassifi ed tumor, suggesting that CT as an imaging technique was unable to characterize most of these tumors.…”
Section: Discussionmentioning
confidence: 89%
“…Although some previous reports suggested sex diff erences in the occurrence of primary brain tumors, a recent study by de Robles et al indicated no statistically signifi cant gender diff erence in the overall estimate of brain tumors 27,28 . Th e most common tumor found in our study was an unclassifi ed tumor, suggesting that CT as an imaging technique was unable to characterize most of these tumors.…”
Section: Discussionmentioning
confidence: 89%
“…Brain tumors include a large group of different benign and malignant neoplasia that arises from the brain parenchyma and adjacent structures [1]. Primary brain cancer is relatively uncommon, representing approximately 2% of all cancers; however, it is often associated with significant disabling and mortality despite the application of all the indicated therapeutic measurements [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial to have independent data from different developing countries in order to better understand the epidemiology of primary brain tumors. However, despite their devastating impact on many patients worldwide, there is lack of systematic reviews of the global prevalence of these tumors [1]. This issue is even more intense in developing countries, where it is often difficult to create accurate population-based cancer registries due to limited infrastructures, low-quality healthcare records, population movements, and political and economic instability [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Primary brain tumors are the most common solid tumors which mainly develop from abnormal cells in the brain [1]. It has been well known that brain tumors are a heterogeneous group of tumors arising from brain parenchyma and its surrounding structures [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well known that brain tumors are a heterogeneous group of tumors arising from brain parenchyma and its surrounding structures [2]. Epidemiologic studies suggested that the prevalence of brain tumors was about 19 per 100,000 person-years, with the incidence of benign tumors and malignant tumors 12 per 100,000 person-years and 8 per 100,000 person-years, respectively [1]. Though there is much progress in the understanding of the molecular pathogenesis of brain tumors, there is still lack of effective treatments for malignant brain tumors [3,4].…”
Section: Introductionmentioning
confidence: 99%